Correlação espacial entre a altitude e as precipitaç ões pluviométricas no estado de São Paulo - Fenille, Mareio Colombo; Cardim, Márcio [UNESP] (My University, 2007)
The rain occurrence is one of the most important phenomena to determinate the climate and, as most of the other climatic phenomena, shows a continuous spatial variability that can be detected through special geostatistical methods. Besides the great influence of the topographic relief on the specific climate of each region, it is normal to expect spatial correlations of this variable with the precipitations; the determinism of this correlation may help to elaborate more precise conclusions involving these phenomena. In this paper, the spatial variability of altitude and of the pluviometric precipitations was rigorously analyzed, besides the existing correlation between these variables. It was concluded that these variables show strong spatial dependence and they are directly correlated. The mapping of the occurrence of both the phenomena was done by geostatistical methods pased on the infomiation concerning the spatial variability of each one.

A ocorrência de precipitação é um dos fenômenos de maior importância na determinação do clima e, como a maioria dos demais fenômenos climáticos, apresenta uma variabilidade espacial contínua que pode ser detectada através de métodos geoestatísticos especiais. Conhecida a grande influência do relevo topográfico no clima específico de cada região, é de se esperar que esta variável apresente correlações espaciais com a ocorrência de precipitações, e que o determinismo desta correlação possa de alguma maneira auxiliar na elaboração de conclusões mais precisas que envolvam estes fenômenos. Neste trabalho analisou-se rigorosamente a variabilidade espacial da altitude e das precipitações pluviométricas, além da correlação existente entre estas variáveis. Concluiu-se que estas variáveis apresentam forte dependência espacial e estão diretamente correlacionadas. O mapeamento da ocorrência de ambos os fenômenos foi realizado também através de métodos geoestatísticos, baseando-se nas informações acerca da variabilidade espacial de cada um. Palavras-chave: The rain occurrence is one of the most important phenomena to determinate the climate and, as most of the other climatic phenomena, shows a continuous spatial variability that can be detected through special geostatistical methods. Besides the great influence of the topographic relief on the specific climate of each region, it is normal to expect spatial correlations of this variable with the precipitations; the determinism of this correlation may help to elaborate more precise conclusions involving these phenomena. In this paper, the spatial variability of altitude and of the pluviometric precipitations was rigorously analyzed, besides the existing correlation between these variables. It was concluded that these variables show strong spatial dependence and they are directly correlated. The mapping of the occurrence of both the phenomena was done by geostatistical methods based on the information concerning the spatial variability of each one. Keywords: Altitude, pluviometric precipitation, semivariogram, cross semivariogram, cokriging. Palavras-chave: Altitude, precipitação pluviométrica, semivariograma, semivariograma cruzado, cokrigagem.
Spatial correlation between altitude and pluviometric precipitations on the São Paulo State
Keywords: Altitude; Cokriging; Cross semivariogram; Pluviometric precipitation; Semivariogram; altitude; precipitation (climatology); spatial variation; topographic effect; Brazil; Sao Paulo [Brazil]; South America